2016
DOI: 10.1097/bsd.0000000000000058
|View full text |Cite
|
Sign up to set email alerts
|

Expansive Laminoplasty Versus Laminectomy Alone Versus Laminectomy and Fusion for Cervical Ossification of the Posterior Longitudinal Ligament

Abstract: Posterior surgeries resulted in clinical improvements although with loss of cervical lordosis in CSM with OPLL patients. OPLL may worsen more frequently after LA. LF and laminoplasty are preferable techniques in this condition, with the former better for patients with high baseline SVA distances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 11 publications
2
66
1
6
Order By: Relevance
“…The authors found a decreased rate of progression in the PDF population compared with laminectomy and/or laminoplasty populations (p < 0.05). 29 Our findings support this hypothesis. We found the incidence of OPLL progression to be statistically significantly lower in the decompression and fusion population compared with the decompression-only population (p < 0.0001).…”
supporting
confidence: 83%
“…The authors found a decreased rate of progression in the PDF population compared with laminectomy and/or laminoplasty populations (p < 0.05). 29 Our findings support this hypothesis. We found the incidence of OPLL progression to be statistically significantly lower in the decompression and fusion population compared with the decompression-only population (p < 0.0001).…”
supporting
confidence: 83%
“…This different result in the subgroup analysis was caused by the relative weighting of the studies in the overall versus the long-term follow-up analysis. In the overall analysis, the studies of Zhang et al 19 and Lee et al 10 had very low weights (less than 2% for each), whereas in the long-term follow-up analysis they were weighted almost equally with the study of Yang et al 18 (approximately 30% each). The reason for this difference was that the study by Woods et al, 17 which had a very narrow standard deviation, was excluded in the long-term follow-up analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A paper "in press" was included. 10 Two reviewers independently assessed the eligibility of all studies retrieved from the databases. Any disagreement between the reviewers was resolved through discussion.…”
Section: Methods Information Sourcesmentioning
confidence: 99%
See 2 more Smart Citations